Integrated data visualisation: an approach to capture older adults' wellness. (18th October 2012) - Le, Thai; Wilamowska, Katarzyna; Demiris, George; Thompson, Hilaire
Informatics tools can help support the health and independence of older adults. In this paper, we present an approach towards integrating health–monitoring data and describe several techniques for the assessment and visualisation of integrated health and well–being of older adults. We present three different visualisation techniques to provide distinct alternatives towards display of the same information, focusing on reducing the cognitive load of data interpretation. We demonstrate the feasibility of integrating health–monitoring information into a comprehensive measure of wellness, while also highlighting the challenges of designing visual displays targeted at multiple user groups. These visual displays of wellness can be incorporated into personal health records and can be an effective support for informed decision–making.